Consensus recommendations for using the Multiplate® for platelet function monitoring before cardiac surgery. (23rd July 2014) - Kong, R.; Trimmings, A.; Hutchinson, N.; Gill, R.; Agarwal, S.; Davidson, S.; Arcari, M.
Summary Patients requiring urgent cardiac surgery are usually already taking antiplatelet drugs including aspirin and a P2Y12 ADP receptor antagonist (e.g., clopidogrel, prasugrel or ticagrelor). This presents clinicians with the challenge of balancing the risk of thrombotic complications, if antiplatelet drugs are stopped before surgery, with the problems of excessive bleeding when surgery is performed in the absence of adequate platelet function. Preoperative platelet function monitoring is able to identify when patients have recovered platelet function. The Multiplate® (multiple electrode impedance platelet aggregometer) is a point of care device that enables monitoring of platelet function. The authors offer recommendations based on real‐world, collective experience in the use of platelet function monitoring. These cover the use of the Multiplate® analyser to predict the need for platelet transfusion in the perioperative period and the individualized waiting period after cessation of P2Y12 ADP receptor antagonists before cardiac surgery.